DETERMINANT FACTORS FOR THE DECISION TO SAVE IN SHARIA BANK - Romandhon, Romandhon; Hujah, Afi Shohibul; Kaukab, M. Elfan; Musfiroh, Mila Fursiana Salma; Purwanto, Heri; Suyono, Nanang Agus (Jurnal 'Ulwan, 2024)
The aim of the research is to determine the influence of knowledge, religiosity, income and culture on savings decisions at Sharia Banks and this phenomenon is the lack of members of the Surau Al-Hidayah taklim assembly who save at the West Kalimantan Sharia Bank. This research uses quantitative research methods. Data collection was carried out by distributing questionnaires to the Al-Hidayah Ngabang Landak congregation, West Kalimantan. The sample used was 60 respondents using the Non-Probability Sampling method or saturated sample. The analytical tool used is multiple linear analysis using the IMB Statistics SPSS version 25 application. The results of this study show that knowledge has a positive effect on the decision to save at a sharia bank. Meanwhile, religiosity, income and culture do not influence the decision to save at a sharia bank. However, simultaneously all variables have a positive influence on the decision to save at a sharia bank.